2017 IEEE Custom Integrated Circuits Conference (CICC) 2017
DOI: 10.1109/cicc.2017.7993623
|View full text |Cite
|
Sign up to set email alerts
|

A 220-mV input, 8.6 step-up voltage conversion ratio, 10.45-μW output power, fully integrated switched-capacitor converter for energy harvesting

Abstract: This paper presents a fully integrated step-up switched-capacitor DC-DC converter for energy harvesting applications. The proposed solution exhibits both a high voltage-conversion ratio and a high power-conversion efficiency from a low-voltage source such as a thermoelectric generator or an indoor solar cell. The circuit has been implemented in TSMC 55nm CMOS process. Measurements demonstrate that it can properly operate with a 220 mV input, providing a 1.9 V output voltage at 10.45 μW output power, with 37.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The resulting r vector, the vector used in eq. 23 which relates switch on-resistance to 1 f sw C out is Relating C oss to the R on of the switch using eq. 25 and substituting in the expression for R on , k switching can be found…”
Section: A 1:5 Sc Converter Design Examplementioning
confidence: 99%
See 2 more Smart Citations
“…The resulting r vector, the vector used in eq. 23 which relates switch on-resistance to 1 f sw C out is Relating C oss to the R on of the switch using eq. 25 and substituting in the expression for R on , k switching can be found…”
Section: A 1:5 Sc Converter Design Examplementioning
confidence: 99%
“…Switched Capacitor (SC) converters have been investigated as solutions in a number of space constrained battery-powered and power harvesting applications [1], [2]. They have been increasingly used in novel multi-stage power management systems [3] and as parts of emerging hybrid converter topologies [4], [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that effective voltage V EFF in relation to R ON acts as argument of exponential function located in denominator, which implicates the substantial sensitivity to change of this quantity. In order to overcome this issue, many techniques such as dynamic control, feed-forward biasing of the bulk electrode, multistage topology, implementation of charge transfer switches (CTS) parallel with pass gate switches (PGS) or backward control of the previous stage by body electrode voltage can be included in the low-voltage CPs design [11][12][13][14].…”
Section: Design Procedures Of Bd Charge Pumpmentioning
confidence: 99%
“…The driver generates a non-overlapping outputs under the condition of non-overlapping control signals (Cl k c and nCl k c ). Design utilizes only two capacitors and charging is accomplished directly by the supply voltage, compared to three capacitors (two capacitors version is also available) with lower driving range of ≈ −V SUPP ÷ V SUPP and charging supported by the clock signal presented in [46]. More details together with the propagation delay measurement of the proposed driver can be found in [45] and [47] respectively.…”
Section: Charge Pump For Self-powered Systemsmentioning
confidence: 99%